Equilibrium Worker-Firm Allocations and the Deadweight Losses of Taxation - Jesper Bagger; Espen R. Moen; Rune Majlund Vejlin (Institute of Labor Economics (IZA), 2021)
We analyse the deadweight losses of tax-induced labor misallocation in an equilibrium model of the labour market where workers search to climb a job ladder and firms post vacancies. Workers differ in abilities. Jobs differ in productivities and amenities. A planner uses affine tax functions to finance lump-sum transfers to all workers and unemployment benefits. The competitive search equilibrium maximizes after-tax utility subject to resource constraints and the tax policy. A higher tax rate distorts search effort, job ranking and vacancy creation. Distortions vary on the job ladder, but always result in deadweight losses. We calibrate the model using matched employer-employee data from Denmark. The marginal deadweight loss is 33 percent of the tax base, and primarily arise from distorted search effort and vacancy creation. Steeply rising deadweight losses from distorted vacancy creation imply that the deadweight loss in the calibrated economy exceeds those incurred by very inequality averse social planners.
Keywords: H21; H30; J63; J64; 330; vacancy creation; job ranking; job search; labour allocation; redistribution; optimal taxation; deadweight loss; amenities; matched employer-employee data